Generation of mCherryBody: an Anti-Transferrin Receptor Antibody Variable Fragment Linked by The Fluorescent Protein mCherry - Kusharyoto, Wien; Andriani, Dian; Handayani, Ira (ANNALES BOGORIENSES, 2016)
A facile generation of a recombinant antibody fragment with intrinsic fluorescent properties of the monomeric fluorescent protein mCherry is described. The so-called mCherryBody was designed based on the structure model of the variable fragment of anti-transferrin receptor antibody LUCA31 and the X-ray crystallographic structure of the protein mCherry. mCherryBody was constructed to retain optimal spatial geometry between the C- and N-termini of the antibody light-chain (VL) and heavy-chain (VH) by mimicking the domains interface pairing in antibody Fab fragments and incorporation of the fluorescent protein mCherry as a bridging scaffold. The gene encoding the chimeric protein was cloned into the pJExpress414 expression vector, expressed and secreted into the periplasm of Escherichia coli NiCo21(DE3) for assembly and disulphide bond formation. Based on its amino acid sequence, mCherryBody was predicted to have a molecular weight of 51.46 kDa. The modular assembly used in the generation of mCherryBody may permit the interchange of binding sites and of fluorescent proteins to create robust panels of coloured antibody fragments. Thus, the mCherryBody platform facilitates rapid generation of colored single-chain variable fragment (scFv) chimeras that could be used for screening of antibodies against cell surface markers or receptors.